Investigation of Washing Mechanisms in Volume-Based Fractional Rain Samples in High Altitude Semirural Site by Determining Polycyclic Aromatic Hydrocarbons, Elemental Carbon, and Organic Carbon. (1st January 2020) - Dörter, Melike; Sağırlı, Eda; Karakaş, Duran; Yenisoy-Karakaş, Serpil
Abstract: Polycyclic aromatic hydrocarbons (PAHs), elemental carbon (EC), and organic carbon (OC) concentrations were investigated in five fractional rain samples collected in the high-altitude semirural site located at Black Sea Region in order to determine the dominant scavenging mechanism and source regions for these pollutants. The contribution of the secondary organic carbon (OCsec ) to the OC concentration was calculated using EC tracer method and confirmed by the help of ozone data. The results showed that the ratio of OCsec to OC was the highest for the 8th April events (68–90%) and the lowest for the 15th April event (37%). The high correlations were found between combustion-related PAHs and EC. Distinct reddish-brown color on filters, dust forecast by BSC-DREAM8b, Sc/Ti ratio, and back trajectory measurements (HYSPLIT) were used to examine the effect of North Africa. Finally, factor analysis (factor loadings and factor scores) results were combined with all findings to determine the effect of local and long range transportation sources.